Istihsan : the doctrine of juristic preference in Islamic law - Kayadibi, Saim (Islamic Book Trust, 2010)
The research work embodied in this thesis constitutes a critical analysis of classical and modern aspects of the concept of istihsān (juristic preference) in Islamic law, an important principle in Islamic legal legislation throughout history. This area of legislation has been investigated by many researchers and scholars; however, the research work conducted to evaluate the true nature and role of istisān with regard a combination of classical and modern approaches still requires further investigation. The thesis consists of four chapters. The introductory chapter is the theoretical basis of the study and comprises a brief understanding of some general principles of Islamic law; the Qur’an, the Sunnah, ijmā‘ (consensus), qiyās (analogy), maslahah mursalah (consideration of public interest), istishāb (presumption of continuity), qawl Sahābī (the saying of the Companion of the Prophet), ‘urf (custom), sadd al- dharā’i‘ (blocking the means), shar‘ man qablanā (revealed laws preceding to the Sharī‘ah of Islam) and istiqrā’ and so on. Chapter II deals with the development of ra’y and ijtihād in the context of istihsān. This chapter introduces the concept of ra’y and ijtihād as related to historical background and implementation, with their methods of development where istihsān originated from. Istihsān was practiced well before the formation of the Islamic legal schools of thought and can be referred back to the time of the Prophet (s), the Companions and the Successors. Chapter III begins with definitions of the term of istihsān, identifying its true nature with an extensive analysis both linguistically and technically. Historical development is investigated, and then the viewpoints of the scholars and their discourses that form the main cornerstone of this study. Also in this chapter the validity of istihsān is discussed and explained with special reference to the reason behind the disagreement over istihsān as the scholars introduce their evidences to justify the claims of those who consider it a valid source of law and those who do not recognize it as such. Consideration of istihsān and its implementation in the early anafī school of thought by eminent scholars is also elaborated. Chapter IV is devoted to the types of istihsān and the division among the scholars with practical examples. Other related terms as ihtiyāj (need), zarar (harm), raf‘ al-haraj (avoiding Hardship), mashaqqah (hardship), Darūrah (necessity).